2019
DOI: 10.3390/su11113009
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Power Output Forecasting Using Least-Squares Support Vector Regression and Google Data

Abstract: Sustainable and green technologies include renewable energy sources such as solar power, wind power, and hydroelectric power. Renewable power output forecasting is an essential contributor to energy technology and strategy analysis. This study attempts to develop a novel least-squares support vector regression with a Google (LSSVR-G) model to accurately forecast power output with renewable power, thermal power, and nuclear power outputs in Taiwan. This study integrates a Google application programming interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Recent papers addressing wind power forecasts could be broadly classified into 5 categories: papers focused on how to increase NWP accuracy [4][5][6][7][8], good-practice prediction guidelines [9][10][11], comparisons of accuracy across prediction models [12][13][14][15], hybrid and ensemble methods [16][17][18][19][20][21][22][23][24][25][26][27], and conventional methods improved by, among other things, preprocessing [28][29][30][31][32][33][34][35]. At this point, clear distinction should be made between hybrid, ensemble and improved models.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent papers addressing wind power forecasts could be broadly classified into 5 categories: papers focused on how to increase NWP accuracy [4][5][6][7][8], good-practice prediction guidelines [9][10][11], comparisons of accuracy across prediction models [12][13][14][15], hybrid and ensemble methods [16][17][18][19][20][21][22][23][24][25][26][27], and conventional methods improved by, among other things, preprocessing [28][29][30][31][32][33][34][35]. At this point, clear distinction should be made between hybrid, ensemble and improved models.…”
Section: Related Workmentioning
confidence: 99%
“…Hybridization [16][17][18][19][20][21] and parallelization [22][23][24][25][26][27] of prediction models use datarefining and error compensation, respectively, as an approach to maximize prediction accuracy. The most common bases for hybrid models in recent literature are ANNs [17][18][19]21] due to their generalization ability, while the most common hybrid add ons would be single optimization methods [16,18,20,21]. With varying implementation, error reduction can be achieved in different ways.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyndman and Fan [20] forecasted the density of long-term peak electricity demand by proposing a new and systematic methodology, and the model outperforms others, as shown by the results of the study. In other research, Chen et al [29] developed a novel least-squares support vector regression with a Google (LSSVR-G) model to predict the power output from various sources in Taiwan, including renewable power, thermal power and nuclear power. The discussion of this study indicated that the proposed LSSVR-G model performs better than any previously studied models with respect to accuracy and stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large-scale, random, intermittent wind power and large-capacity nuclear power plants are connected to the power grid, which puts higher requirements on the climbing rate of units such as thermal power [9,10]. With the continuous increase of peak-valley difference of load in coastal areas and the construction and development of wind and nuclear power units, the pressure of peak shaving in coastal areas will be seriously aggravated and the demand for wind and nuclear power to participate in daily peak shaving is becoming stronger [11][12][13].…”
Section: Introductionmentioning
confidence: 99%